Analisis Persepsi Mahasiswa Terhadap Pengelolaan Keuangan Pribadi : Studi Kasus Di Kalangan Mahasiswa Stain Bengkalis - Ramadhan, Muhammad Rizky; Sagita, Nadra (Yayasan Rahmat Islamiyah, 2024)
This study aims to analyze students' perceptions of personal financial management at the State Islamic College (STAIN) Bengkalis. Good personal financial management is important for students to achieve financial well-being and avoid financial problems in the future. This study used qualitative methods by distributing questionnaires and conducting interviews with STAIN Bengkalis students to collect data related to their knowledge, attitudes, and behavior in managing personal finances. The results of this study are expected to provide an overview of student perceptions of personal financial management and become a consideration for the campus in developing financial education programs that suit student needs.